Practical Plumbing Engineering - Harris,Cyril M. (American Society of Plumbing Engineers, 1998)
Annotation Fifteen specialists in the field contribute material on their areas of expertise. Focusing on the plumbing systems used in both residential and commercial facilities, they examine a wide variety of aspects, ranging from the basics of water quality, treatment, supply, distribution, and pressure to the latest developments in earthquake protection, cross-connection control, and the specifications for plumbing systems. Annotation copyrighted by Book News, Inc., Portland, OR.
Keywords: elektronické knihy; electronic books